2014
DOI: 10.4103/0971-6203.139011
|View full text |Cite
|
Sign up to set email alerts
|

MRC5 and QU-DB bystander cells can produce bystander factors and induce radiation bystander effect

Abstract: Radiation damages initiated by radiation-induced bystander effect (RIBE) are not limited to the first or immediate neighbors of the irradiated cells, but the effects have been observed in the cells far from the irradiation site. It has been postulated that bystander cells, by producing bystander factors, are actively involved in the propagation of bystander effect in the regions beyond the initial irradiated site. Current study was planned to test the hypothesis. MRC5 and QU-DB cell lines were irradiated, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…One states that these effects increase with dose, while the other argues that they do not. Some researchers suggest that the effects reach a saturation point at low doses and no further effects are seen at higher doses [ 104 , 115 , 116 ]. Others consider that a binary response, with a clear threshold dose below which no effects are observed, is also possible [ 104 ].…”
Section: Signal-mediated Effects In Plantsmentioning
confidence: 99%
“…One states that these effects increase with dose, while the other argues that they do not. Some researchers suggest that the effects reach a saturation point at low doses and no further effects are seen at higher doses [ 104 , 115 , 116 ]. Others consider that a binary response, with a clear threshold dose below which no effects are observed, is also possible [ 104 ].…”
Section: Signal-mediated Effects In Plantsmentioning
confidence: 99%
“…Additionally, different sensitivity of organs leads to different carcinogenesis risks years after exposure [38]. Different effects induced by the bystander effect in different cell types have been observed in in-vitro studies [39-41]. In-vivo studies which have confirmed the expression of carcinogenesis markers in non-targeted tissues is deemed to be different.…”
Section: Introductionmentioning
confidence: 99%